1999
DOI: 10.1029/1998gl900227
|View full text |Cite
|
Sign up to set email alerts
|

Blob instability in rotating compositional convection

Abstract: Abstract. The onset and structure of compositional convection in a rotating system are investigated experimentally. A vertically oriented cylindrical annulus filled with NH4 C1-H20 solution is cooled from the bottom and can be rotated about its axis at rates ranging up to 10.5 rad s -x corresponding to Ekman numbers down to 7.5 x 10 -6. The Coriolis force has a strong effect on the structure of plumes above the mush-liquid interface. Helical motion of the conduit, which is weakly developed in the non-rotating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…However, it is likely that any such plume is unstable (e.g., see Eltayeb and Loper, 1997;Classen et al, 1999;Eltayeb et al, 2005), leading to the production of a sequence of plumes governed by the equations presented above. However, it is likely that any such plume is unstable (e.g., see Eltayeb and Loper, 1997;Classen et al, 1999;Eltayeb et al, 2005), leading to the production of a sequence of plumes governed by the equations presented above.…”
Section: Scaling and Structure Of Plumesmentioning
confidence: 99%
“…However, it is likely that any such plume is unstable (e.g., see Eltayeb and Loper, 1997;Classen et al, 1999;Eltayeb et al, 2005), leading to the production of a sequence of plumes governed by the equations presented above. However, it is likely that any such plume is unstable (e.g., see Eltayeb and Loper, 1997;Classen et al, 1999;Eltayeb et al, 2005), leading to the production of a sequence of plumes governed by the equations presented above.…”
Section: Scaling and Structure Of Plumesmentioning
confidence: 99%
“…The study of fluid motions induced during the directional solidification of fluid alloys has received considerable attention over the past four decades (Copley et al 1970, Loper 1978, Huppert and Worster 1985, Loper 1987, Huppert 1988, 1990, Worster 1992, 1997, Hellawell et al 1993, Eltayeb and Loper 1994, 1997, Eltayeb and Hamza, 1998, Eltayeb 1999, Jellinek et al 1999, Classen et al 1999, Morse 2000, Eltayeb et al 2004, 2005 (hereinafter referred to as EHJKL), Eltayeb 2006). These studies include theoretical and experimental investigations relating to diverse applications ranging from metallurgy to geophysics.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Eltayeb and Hamza (1998) on the stability of a vertically rotating cylindrical plume of circular cross-section showed that the presence of rotation increased the growth rate by an order of magnitude, from O(R) in the absence of rotation to O(1) when rotation is present. Classen et al (1999) studied experimentally plumes rising from a mushy layer in a vertically rotating fluid to find that the plumes are bent by the rotation and break up into blobs. Noting that stability properties of a Cartesian plume are qualitatively similar to those of a cylindrical plume of circular cross-section in similar surroundings, Elbashir et al (2010) studied the stability of two interacting Cartesian plumes to find that they possess a growth rate of O(1) on the convective time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of publications have addressed the dynamics of compositional plumes (see, e.g. Eltayeb and Loper 1997, Classen et al 1999, Eltayeb 2006. Eltayeb and Loper (1991, 1994, 1997 studied the stability of compositional plumes rising in a fluid of infinite extent to find that a plume is always linearly unstable for all non-zero Grashoff numbers, R, where the Grashoff number is the ratio of buoyancy to viscous forces.…”
Section: Introductionmentioning
confidence: 99%